Effect of cadmium chloride on some biochemical parameters of liver, testes and adrenal glands of rats - Ганусова, Г. В.; Охріменко, С. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The effect of chronic (1 mg/kg of body weight, 28 days), single – 0.6 mg/kg of b. w. and combined administration of cadmium chloride on protein level and content of TBA-reactive products and thiol groups in testes and adrenal glands, as well as tyrosine transaminase activity of rat liver was investigated. Adrenal glands weight increased when cadmium chloride administered chronically (1 mg/kg, 28 days), and testes mass did not change in all groups. Increased adrenal glands mass is usually observed at prolonged exposure to stress factors. After administration of cadmium chloride at a dose of 0.6 mg/kg, with chronic administration of CdCI2 there were revealed elevated levels of TBA-reactive products (121%) in testes, as well as reduced content of non-protein thiol groups (63%) in adrenal glands of rats, in other experimental groups significant changes of studied parameters were not found. When a salt of cadmium enters the body, increase of TBA- reactive products content and reduction of thiols in investigated glands indicate an imbalance in the system of prooxidants-antioxidants. Activity of liver tyrosine transaminase was increased in animals of all experimental groups, which may indicate stress effect of cadmium compounds.